Acute Lethal Toxicity Test of Cd2 + Against Gambusia (Gambusia affinis) and Influence on Protease Activity - Yuliana; I Gusti Ngurah Putu Utama; Moh. Awaluddin Adam (Faculty of Science and Technology University Ibrahimy, 2020)
Cadmium the form of undamaged elements but can change shape to different compounds. The low concentrations of toxic cadmium for all life, including plants, fish, birds, mammals (including humans), and microorganisms. The purpose of this research is to know the value of LC50-96 hours Cd2+ on test biota. The test biota was Gambusia fish (Gambusia affinis), the test biota can represented the actual state of the environment. The study was divided into two stages, namely preliminary test and acute lethal toxicity (LC50-96 hours), each treatment repeated three times. Acute lethal toxicity test data were analyzed probit. The results showed that the value of LC50-96 hours Cd2+ to fish gambusia was 0.03 ppm. While in the protease activity of cadmium exposed preliminary fish increased activity from the control fish.